El ingeniosos mundo de las PYMES (2010)
Summary form the start, launch of economic opennes as platform domestic towards globalization, emerging countries as Colombia star addressing pólices which promote the creation of programs to strengthen and encourage entrepreneurship. The Mipymies as productive forcé come and participate in those new public policies to strengthen and implement their business plans